PERAN GURU DALAM MEMPERSIAPKAN LINGKUNGAN BELAJAR ANAK PADA TAHAP PERIODE SENSITIF DENGAN METODE MONTESSORI - Gupita Sari, Cindy; Laurensia Clara Lustia Sari; Intan Pinesti; Andri Anugrahana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Sensitive periods in children occur within a very short period of time and significantly influence a child's abilities. In learning, children construct themselves through physical activities within their surroundings. This research is conducted with the aim of enhancing knowledge about 1) self-construction in children, 2) sensitive periods, and 3) the role of teachers in preparing the learning environment. The results of this research indicate that 1) children construct themselves through physical activities involving their senses, 2) sensitive periods are sensitive times for children to receive stimuli from their surrounding environment, and 3) teachers play an important role in preparing a learning environment using the principles of the Montessori method that is effective for children according to their stage of development.